Bimbingan Teknis Aplikasi Pemasaran Bagi UKM Karang Taruna - Pertala, Erik Candra (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2023)
Technical guidance on marketing applications is one solution to the problems faced by SMEs in Karang Taruna, namely the lack of understanding and use of marketing applications. The purpose of this activity is to improve understanding and skills in using websites and marketing applications to SMEs Karang Taruna Kelurahan Jaya Mekar. The method of implementing this activity is technical guidance to SMEs Karang Taruna, Kelurahan Jaya Mekar. The partner in this bimtek activity is Lurah Keluraha Jaya Mekar. The evaluation was carried out by the direct practice of using marketing applications to Bimtek participants after delivering the material, and the result was that the ability and understanding of the participants increased by 41.66%.